Maternal attachment, emotion-regulation and cognitive functioning of institutionalized children in Malaysia - Syed Mustafa, Siti Zakiah (2017)
At least 40% of Malaysians suffer from mental illness as a result of poor mental health. Mental health and depression are associated to cognitive functioning among youth and older people in a way that higher cognitive functioning leads to better mental health. To date, prevalence of depression among adolescents and children in institutional care is known but cognitive functioning of children has yet to be identified. Cases of children abuse reported on mother as the main perpetrator has been increasingly alarming and has caused a major concern to the society, which one of the reasons is the problem in early attachment between mother and child. Attachment with a primary caregiver in an early age of a child’s life is vital for current and later functioning of the child. Children in secure attachment are more likely to demonstrate excellency in various developmental functioning when compared to those who are insecurely attached (e.g., maltreated children). Past studies documented that children with insecure attachment would experience lower cognitive functioning (e.g., low IQ, poor academic and school performances) when compared to the non-maltreated. Nonetheless, other factors that contribute to the institutionalized children’s cognitive functioning, specifically, in the Malaysian context are less understood. Thus, the present study is undertaken to investigate the relationship between maternal attachment (trust, communication, and alienation) and cognitive functioning among the institutionalized children in Malaysia; and the mediating role of emotion-regulation on these relationships. A total sample of 262 institutionalized children aged 7 to 12 years (mean age= 10.09) was recruited using probability proportional to size (PPS) sampling from six selected states in Malaysia, representing Peninsular (Perak, Pahang, Kuala Lumpur and Pulau Pinang) and East Malaysia (Sabah and Sarawak). The children provided data using self-administered and researcher-administered questionnaires, due to variation in reading ability and then responded to a series of measures including the Inventory of Parent and Peer Attachment-Revised (IPPA-R) for Children, the Raven’s Coloured Progressive Matrices (RCPM) and the Emotion-Regulation Inventory for Children and Adolescent (ERICA). The data were analysed using partial least squares – structural equation modelling (PLS-SEM) in SmartPLS 3.0 software to examine direct relationships between maternal attachment (trust, communication, and alienation) and cognitive functioning, and indirect effects through emotion-regulation. Results revealed that alienation was positively correlated to cognitive functioning, whereas, insignificant relationship was found for trust and communication. This study also found that emotion-regulation was correlated to alienation and cognitive functioning, which was consistent with previous studies. The findings suggested that alienation is the contributor of healthier cognitive functioning among the institutionalized children in Malaysia. Furthermore, the findings indicated the consequential role of emotionregulation in influencing the association between alienation and cognitive functioning. In other words, children in the institutions are influenced by the efforts of modulating emotional arousal in order to aid better cognitive performance. According to the theory, high quality of maternal attachment, which is secure attachment tends to support a child’s ability to involve further in higher order cognitive processes, however among the institutionalized children, an insecure form of attachment (i.e. alienation) was evidenced to support a child’s involvement in the cognitive processes. Further, the findings contribute to the body of knowledge, most notably by demonstrating the potential factors that influence the institutionalized children’s cognitive functioning, which would be valuable for clinicians, researchers, policy makers, and the public at large.